Refugee Protection in India: An Analysis of International Obligations and Domestic Practice in Contemporary Periods (Journal of Advances and Scholarly Researches in Allied Education, 2026)
India hosts one of the largest refugee populations in South Asia, yet remains conspicuously absent from the 1951 Refugee Convention and its 1967 Protocol. In the absence of dedicated domestic legislation, refugees in India are governed by a patchwork of colonial-era statutes designed for foreigners, leaving them vulnerable to arbitrary detention, deportation, and systemic denial of basic rights. This article critically examines the international legal obligations India bears toward refugees, the constitutional and judicial protections that have partially filled the legislative vacuum, the structural inadequacies of existing domestic law, and the role of international and national human rights bodies. It further analyses the contemporary challenges posed by the Rohingya crisis and the Citizenship Amendment Act, 2019 (CAA), arguing that India's ad hoc approach is no longer tenable. The article concludes by advocating for the enactment of a dedicated national refugee law and the development of a South Asian regional refugee framework.